Application of mineral admixtures and steel fibers in experimental compositions for reactive powders concrete (Research, Society and Development, 2021)
Concrete is a material used in various applications, involving paving, sanitation, infrastructure and superstructure works, dams, bridges, and architectural elements, but for certain applications their physical and mechanical properties are affected by intense degradation agents, motivating the search for artifacts that improve these properties and increase the useful life and durability of matrix materials cement industry. The objective of this work is to clarify the influence of different mix of superplasticizer, steel fibers, water/cement factor, different types of mineral admixtures, besides the type of thermal treatment and method of cylindrical concrete molds of reactive powders, evaluating the resistance to axial compression at the ages of 7 and 14 days. 17 compositions were defined, by mass, for the manufacture of concretes, divided into two stages: the first composed of 10 compositions, and the second by 7 compositions. It was used CP-V ARI cement, sand, metakaolin, silica fume, superplasticizer and kneading water with temperature between 1 and 3°C. After the conformation of the cylindrical molds of dimensions 5x10cm with the aid of a portable immersion vibrator, the specimens were unmolded after 24 hours and received thermal treatment with periods of pre-cure and isotherm that varied according to the defined trait. According to the results obtained, the reduction of the w/c factor and the superplasticizer additive presented higher resistance to compression, however, this reduction in an excessive way impairs the hydration process, implying in the incomplete hydration of all the cement particles, resulting in less resistance. It was observed that the application of thermal treatment and densification by means of layer immersion vibrators acted as essential factors in the increase of the resistances, and that the isotherm time of the composite corroborates the respective increase, until its stabilization, in the temperatures studied.